2022
DOI: 10.1111/cid.13157
|View full text |Cite
|
Sign up to set email alerts
|

Implant deformation and implant–abutment fracture resistance after standardized artificial aging: An in vitro study

Abstract: Background and purpose: Zirconia abutments have been widely adopted in clinical implant practice. The unique mechanical properties of zirconia may significantly affect the long-term prognosis of implant treatments. The purpose of this study was to investigate the influence of abutment material on implant deformation and fracture resistance of internal conical connection implant-abutment complexes of two diameters after standardized artificial aging.Materials and methods: Thirty original abutments (one-piece ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
(111 reference statements)
0
0
1
Order By: Relevance
“…Further investigation revealed that utilizing a pair of 3.5 mm implants led to reduced surface strain when compared with only one 5 mm implant. This signified that the double implant technique surpassed the single implant method [57]. In contrast, our findings demonstrated that two 3.5 mm implants in-duced higher levels of cortical bone stress under lateral loading than a single 5.0 mm implant.…”
Section: Discussioncontrasting
confidence: 56%
“…Further investigation revealed that utilizing a pair of 3.5 mm implants led to reduced surface strain when compared with only one 5 mm implant. This signified that the double implant technique surpassed the single implant method [57]. In contrast, our findings demonstrated that two 3.5 mm implants in-duced higher levels of cortical bone stress under lateral loading than a single 5.0 mm implant.…”
Section: Discussioncontrasting
confidence: 56%